Does Household Borrowing Reduce the Trade Balance? Evidence from Developing and Developed Countries - Can Xu; Jan Jacobs; Jakob de Haan (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We examine the dynamic impact of household borrowing on the trade balance using data from 33 developing countries and 36 developed countries over the 1980-2017 period. Our findings suggest that the impact of household borrowing on the trade balance is by and large negative, both in the short and long run. We show that household borrowing's adverse effects on the trade balance are more pronounced but less persistent in developing countries.
Keywords: E21; F32; G21; 330; household borrowing; trade balance; dynamic effects; panel ARDL model